Exploring Emerging Trends in Technology and Their Impact on Society - Hamdard, Mohammad Salim; Samadzai, Abdul Whid (Journal of Natural Sciences – Kabul University, 2024)
Technological advancements have transformed how we live, work, and interact with the world around us. This article examines recent developments in various technological fields and their significant impact on society. Innovations such as artificial intelligence and blockchain have revolutionized industries and profoundly affected daily human life. As we navigate this era of technological revolution, society must embrace these changes while considering their broader implications. Balancing innovation with social and ethical considerations is essential for shaping a positive and sustainable future. We can work towards ensuring a better future for all through responsible progress.